Density functional theory and beyond for band-gap screening: Performance for transition-metal oxides and dichalcogenides - Li, Wenqing; Walther, Christian F. J.; Kuc, Agnieszka; Heine, Thomas (Journal of Chemical Theory and Computation, 2013)
The performance of a wide variety of commonly used density functionals, as well as two screened hybrid functionals (HSE06 and TB-mBJ), on predicting electronic structures of a large class of en vogue materials, such as metal oxides, chalcogenides, and nitrides, is discussed in terms of band gaps, band structures, and projected electronic densities of states. Contrary to GGA, hybrid functionals and GGA+U, both HSE06 and TB-mBJ are able to predict band gaps with an appreciable accuracy of 25% and thus allow the screening of various classes of transition-metal-based compounds, i.e., mixed or doped materials, at modest computational cost. The calculated electronic structures are largely unaffected by the choice of basis functions and software implementation, however, might be subject to the treatment of the core electrons. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20